2012
DOI: 10.1093/nar/gks370
|View full text |Cite
|
Sign up to set email alerts
|

A twist in the tail: SHAPE mapping of long-range interactions and structural rearrangements of RNA elements involved in HCV replication

Abstract: The RNA structure and long-range interactions of the SL9266 cis-acting replication element located within the NS5B coding region of hepatitis C virus (HCV) were determined using selective 2′-hydroxyl acylation analysed by primer extension. Marked differences were found in the long-range interactions of SL9266 when the two widely used genotype 2a JFH-1 (HCVcc) and genotype 1b Con1b sub-genomic replicon systems were compared. In both genomes, there was evidence for interaction of the sub-terminal bulge loop of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
133
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(150 citation statements)
references
References 51 publications
14
133
3
Order By: Relevance
“…Our data confirm previous hypotheses that suggested a kissing complex between 5BSL3.2 and SL2, but they do not agree with the results from NMR analysis (Friebe et al 2005) or SHAPE mapping on the HCV genotype 1b (isolate Con1) (Tuplin et al 2012). No interaction was detected by NMR assays with the same short RNA sequences that we used, and a unique secondary structure was proposed for SL2.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Our data confirm previous hypotheses that suggested a kissing complex between 5BSL3.2 and SL2, but they do not agree with the results from NMR analysis (Friebe et al 2005) or SHAPE mapping on the HCV genotype 1b (isolate Con1) (Tuplin et al 2012). No interaction was detected by NMR assays with the same short RNA sequences that we used, and a unique secondary structure was proposed for SL2.…”
Section: Discussioncontrasting
confidence: 87%
“…These interactions were characterized either in a bimolecular context with the 5BSL3.2-SL2 and 5BSL3.2-Seq9110 complexes or in a trimolecular context with the 5BSL3.2-SL2-Seq9110 ternary complex. In contrast with previous results obtained by NMR spectroscopy with the same short RNA sequences that we used in this work (Friebe et al 2005) or SHAPE mapping with longer RNAs (Tuplin et al 2012), we show that 5BSL3.2 can form a complex with SL2 through kissing-loop interactions. The internal loop of 5BSL3.2 is also able to hybridize with Seq9110.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The terminal-loop of SL9266 forms a 'kissing-loop' interaction with stem loop SL9571 (alternatively SL2) in the 39NCR (Friebe et al, 2005). The 'kissing-loop' is a dynamic structure forming open and closed conformations, both of which are essential for efficient virus replication (Tuplin et al, 2012). We have shown that the closed conformation stimulates HCV IRES initiated translation (Tuplin and others, unpublished results) and the open structure preferentially binds cellular protein EWSR1 upregulating genome replication (Oakland et al, 2013).…”
Section: Initiationmentioning
confidence: 95%